2014
DOI: 10.1007/s10863-014-9541-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phosphorylated form of 2′, 3′-cyclic nucleotide 3′-phosphodiesterase (CNPase) as 46 kDa phosphoprotein in brain non-synaptic mitochondria overloaded by calcium

Abstract: In our previous studies phosphorylation of several membrane-bound proteins in brain and liver mitochondria were found to be regulated by Ca(2+) as a second messenger. One of the proteins, the 46 kDa phosphoprotein was found to be highly phosphorylated when Ca(2+)-induced permeability transition pore (mPTP) was opened in rat brain mitochondria (RBM). In the present study the 46 kDa phosphoprotein was identified as 2',3'-cyclic nucleotide 3'-phosphodiesterase (CNPase) after purification by 2D diagonal electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…6 shows a semi-quantitative analysis of the phosphoprotein bands from SDS–PAGE after separation of Ca 2+ -loaded RBM in the presence or absence of Cbx and anti-TSPO antibody. We investigated the concentration-dependent effect of Cbx on protein phosphorylation and found that Cbx at 1 µM and 10 µM significantly stimulated the incorporation of [γ- 32 P]ATP into 43–46 kDa proteins (where Cx43 and CNP were found) [6,27], 17 kDa proteins (myelin basic protein isoforms) [28], as well as of 3.5 kDa (subunit c of ATP synthase) (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 shows a semi-quantitative analysis of the phosphoprotein bands from SDS–PAGE after separation of Ca 2+ -loaded RBM in the presence or absence of Cbx and anti-TSPO antibody. We investigated the concentration-dependent effect of Cbx on protein phosphorylation and found that Cbx at 1 µM and 10 µM significantly stimulated the incorporation of [γ- 32 P]ATP into 43–46 kDa proteins (where Cx43 and CNP were found) [6,27], 17 kDa proteins (myelin basic protein isoforms) [28], as well as of 3.5 kDa (subunit c of ATP synthase) (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation status of these proteins and peptide was shown to change depending on the opened/closed state of the pore [26]. These phosphoproteins were identified: 46 kDa phosphoprotein is 2′,3′-cyclic nucleotide-3′-phosphodiestearase [27], 21 kDa and 17 kDa phosphoproteins are isoforms of myelin basic protein (MBP) [28], and the 3.5 kDa phosphopeptide is subunit c of ATP synthase [29]. Incubation of the rat brain mitochondria (RBM) with anti-TSPO antibodies specifically prevented these phosphorylations, suggesting that TSPO participates in the modulation of mPTP opening.…”
Section: Introductionmentioning
confidence: 99%
“…Beutner and coauthor suggested that CyP-D regulated the activity of oxidative phosphorylation, presumably altering the activity of the respiratory chain and respirasome assembly and inhibiting the activity of ATP synthase and synthasome assembly of ETC complexes [34]. Earlier, we showed that CyP-D was co-localized with 2 ,3 -cyclic nucleotide-3 -phosphodiasterase (CNPase) in rat brain and liver mitochondria (RBM, RLM) [35], which was identified in our laboratory [36]. We observed that CNPase was associated with each complex of ETC, was colocalized with the adenine nucleotide translocator (ANT), voltage-dependent anion channel, CyP-D, and α-tubulin [35], and performed the protective function in RBM and RLM [37,38].…”
Section: Introductionmentioning
confidence: 70%
“…This could be a consequence of haploinsufficiency for Cnp in animals expressing Cnp Cre/+ , since the Cre recombinase is knocked‐in in one of the Cnp alleles (Lappe‐Siefke et al, ). The molecular function of CNP in myelinating glia is still unknown, but CNP was identified in the mitochondrial fraction, might play a role in mitochondrial permeability (Azarashvili et al, ; McFerran & Burgoyne, ), and can have a neuroprotective function in OLs (Verrier et al, ). Interestingly, mice deficient or haplodeficient for Cnp developed axonal swelling and neurodegeneration in the nervous system at 3.5 months and 19 months, respectively (Hagemeyer et al, ; Lappe‐Siefke et al, ), two features also observed in Pdha1 f/Y ; Cnp Cre/+ axonopathy.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a consequence of haploinsufficiency for Cnp in animals expressing Cnp Cre/1 , since the Cre recombinase is knocked-in in one of the Cnp alleles(Lappe-Siefke et al, 2003). The molecular function of CNP in myelinating glia is still unknown, but CNP was identified in the mitochondrial fraction, might play a role in mitochondrial permeability(Azarashvili et al, 2014;…”
mentioning
confidence: 99%